(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The problem of a pathology of a thyroid gland at rheumatic diseases, in particular at rheumatoid arthritis, remains actual and to this day. The work purpose was studying antitelogenesis to thyroid hormones at patients with mixt autoimmune pathology. In whey of blood of patients with RA and autothyroid pathology are found out antibodies (AB) to Т3 and Т4, their concentration correlates with activity of pathological process. It is shown, that level AB to Т3 and Т4 authentically differs from the maintenance of the given antibodies in whey of blood of healthy faces. Level of antibodies to thyroid hormones can be considered as the criterion predicting development of pathology of a thyroid gland at patients with RA.